Development of an Augmented Reality-Assisted E-Module as an Interactive Visualization Medium for Atomic Model Development Concepts - Faiza Anindya Putri; Bayu Saputra; Annisa Meristin (Universitas Lampung, 2026)
Atomic model development is considered an abstract topic, making it difficult for students to understand. One approach to facilitating the visualization of these concepts is the use of an Augmented Reality (AR)-assisted e-module. This study aimed to describe the validity, practicality, and effectiveness of an AR-assisted e-module on atomic model development concepts for tenth-grade senior high school students. The study employed a Research and Development (R&D) method using the 4D model (Define, Design, Develop, and Disseminate), which was limited to the Develop stage. Product validity was assessed through evaluations by material and media experts. Practicality was measured using teacher perception questionnaires, student response questionnaires, and learning implementation observation sheets. Effectiveness was determined based on the N-gain score. The research participants were students of class X.1 at SMA Negeri 1 Abung Semuli. The results showed that the e-module achieved validity percentages of 90.75% from material experts and 90.00% from media experts, both categorized as very valid. The practicality assessment yielded percentages of 96.20% from teachers, 89.85% from students, and 89.28% from learning implementation observations, all categorized as very practical. The effectiveness of the e-module was indicated by an N-gain score of 0.43, which falls into the moderate category. Based on these findings, the developed AR-assisted e-module is considered valid, practical, and effective, making it suitable for use as a chemistry learning medium on atomic model development concepts.